Steam Explosion Impact to Technical Hemp Fiber Diameter (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Microfibers and nanofibers from natural products have high mechanical properties. For this reason researchers pay particular attention to the natural fibers and to the method how they are obtained. In the research samples with different treatments (alkaline pretreatment, steam explosion and water extraction) were investigated to evaluate treatment influence on fiber diameters. Fractionation does not provide actual results of fibers diameter as thinner fibers agglomerate to each other and around thicker fibers and cannot be sieved. Fiber diameter measurement with an optical microscope shows that pretreatment and treatment reduced the thickest fiber percentage and increase the number of fine particles. Dew-retted hemp gives 16% of thicker fibers and only 39% fibers with a diameters less than 63µm. 50% of alkaline pretreated and steam explosion treated fibers diameters are less than 63 µm and only 8% of diameters fall in range 160 - 630 µm.